2000
DOI: 10.1128/iai.68.12.6826-6832.2000
|View full text |Cite
|
Sign up to set email alerts
|

Naive Human T Cells Develop into Th1 Effectors after Stimulation withMycobacterium tuberculosis-Infected Macrophages or Recombinant Ag85 Proteins

Abstract: Most studies of human T-cell responses in tuberculosis have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
2
14
1
Order By: Relevance
“…Despite past studies demonstrating that T cells are pivotal in the progression of mycoplasma respiratory disease (11), little is known about the T cell responses and their association with pathogenesis of any mycoplasma disease. In particular, the activation of Th1 and Th2 cell subsets has not been examined in any mycoplasma disease, despite their impact in the progression and pathology of other diseases (27)(28)(29)(30)(31)(32)(33)(34)(35). Because of the critical role that T cell responses have in modulating immunity, it is important to ascertain which T cell populations are responding to the mycoplasma infection and their contribution to disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite past studies demonstrating that T cells are pivotal in the progression of mycoplasma respiratory disease (11), little is known about the T cell responses and their association with pathogenesis of any mycoplasma disease. In particular, the activation of Th1 and Th2 cell subsets has not been examined in any mycoplasma disease, despite their impact in the progression and pathology of other diseases (27)(28)(29)(30)(31)(32)(33)(34)(35). Because of the critical role that T cell responses have in modulating immunity, it is important to ascertain which T cell populations are responding to the mycoplasma infection and their contribution to disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Th2 cells control Ab responses through their secretion of characteristic cytokines (e.g., IL-4). Studies have shown that Th cell subset activation is important in the control of other infectious diseases (27)(28)(29)(30)(31)(32)(33)(34)(35), but their impact on mycoplasma respiratory disease is unknown. In addition, CD8 ϩ T cells are also known to impact on the progression of inflammatory diseases, as they can regulate these responses (36,37) or cause lung injury through CD8 ϩ T cell-mediated apoptosis (38 -40).…”
mentioning
confidence: 99%
“…There are several reports describing the cloning and expression of the CFP-10 gene in different expression vectors such as pUC18 (12), pRSETB (13), pGEMt-Easy vector, pVAX1 (14), pMCT6 (15) and pET17b (16). In a series of studies Lakey et al, reported cloning and expression of Ag85A and Ag85B.…”
Section: Discussionmentioning
confidence: 99%
“…To clone this gene, they digested plasmid vector and performed insertion with restriction enzyme KpnΙ (12). Similarly, other researchers used this technique (double cut) to clone this gene (13,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] The present studies are concerned with the delivery of proteins for local activity, specifically the delivery of subunit vaccines to elicit cell-mediated responses for tuberculosis prevention. 22 Many of these proteins are in limited supply and a formulation strategy requires an approach validated using model proteins. The enzyme, β-glucuronidase (GUS), was evaluated as a model protein in preliminary studies of liposome formulation, lyophilization, micronization, and aerodynamic size distributions.…”
Section: Introductionmentioning
confidence: 99%